2017
DOI: 10.1042/bcj20170469
|View full text |Cite
|
Sign up to set email alerts
|

A novel image-based high-throughput screening assay discovers therapeutic candidates for adult polyglucosan body disease

Abstract: Glycogen storage disorders (GSDs) are caused by excessive accumulation of glycogen. Some GSDs (Adult Polyglucosan Body Disease (APBD), Tarui and Lafora diseases) are caused by intracellular accumulation of insoluble inclusions, called polyglucosan bodies (PB), which are chiefly composed of malconstructed glycogen. We developed an APBD patient skin fibroblast cell-based assay for PB identification, where the bodies are identified as amylase-resistant periodic acid-Schiff’s (PAS) stained structures, and quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…As PB quantity was not compared before and after treatment, it remains unclear whether the observed difference in PB quantity was exclusively due to treatment-dependent halting of PB formation or whether some form of polyglucosan degradation occurred. Nevertheless, it was shown that, in cell culture, guaiacol treatment was able to reduce glycogen that was deemed amylase resistant under the experimental conditions (Solmesky et al, 2017; Kakhlon et al, 2018). Whether this effect is attributable exclusively to GYS1 inhibition remains to be determined.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As PB quantity was not compared before and after treatment, it remains unclear whether the observed difference in PB quantity was exclusively due to treatment-dependent halting of PB formation or whether some form of polyglucosan degradation occurred. Nevertheless, it was shown that, in cell culture, guaiacol treatment was able to reduce glycogen that was deemed amylase resistant under the experimental conditions (Solmesky et al, 2017; Kakhlon et al, 2018). Whether this effect is attributable exclusively to GYS1 inhibition remains to be determined.…”
Section: Resultsmentioning
confidence: 97%
“…Five consecutive washes were performed with 150 μL of cold EtOH (66% v/v) followed by drying in a37°C incubator for 30 min. Scintillation fluid (50 μL, PerkinElmer) was added to each well and the 14 C signal was read using the TopCount microplate scintillation and luminescence counter (PerkinElmer) (Solmesky et al, 2017). …”
Section: Star⋆methodsmentioning
confidence: 99%
“…Thus, the discovery of guaiacol as both a PGB reducer and a mild GYS inhibitor is promising in terms of future regulation and therapeutic application not only to APBD but also to the other PGB-involving GSDs -AD, LD, and TD. Interestingly, the majority of PGB reducers recently discovered by us in another APBD patient cell-based HTS (26) were also mild GYS inhibitors. Regulatory considerations for the implementation of guaiacol as a drug for APBD and other GSDs.…”
Section: Gys Downregulation By Guaiacol As a Novel Strategy For Treatmentioning
confidence: 94%
“…Fluorescence images were taken with an IN Cell Analyzer 2000 (GE Healthcare) using a ×10 lens and analyzed with an image analysis protocol developed using the Multi-Target Analysis module of the IN Cell Analyzer Workstation (GE Healthcare). PGB staining of APBD patient-derived skin fibroblasts was done as previously described (26).…”
Section: Gys Downregulation By Guaiacol As a Novel Strategy For Treatmentioning
confidence: 99%
“…Moreover, they provide neither temporal information about when the chemical perturbations are taking effect, nor dynamical information about how the effects evolve as a function of time. Fluorescent labeling, although undoubtedly emerging and powerful [ 2 ], especially when combined with advanced and robust data analytics [ 3 , 4 ], requires an extra step of adding reagents. This may result in undesirable interferences either with the drugs or natural cellular functions, as well as cellular perturbations due to repeated UV light exposure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%